Friends and Helpers - Eddy, Sarah J. (Sarah Jane), 1851-1945 (Salt Lake City, UT : Project Gutenberg, 2004)
"Friends and Helpers" by Sarah J. Eddy is a compilation aimed at teaching children about compassion and kindness toward animals, written in the late 19th century. This educational work seeks to instill a sense of responsibility in children regarding the treatment of all living creatures, presenting various stories and perspectives on the relationships between humans and animals, particularly focusing on dogs, cats, and horses. The opening of the book introduces thematic elements surrounding kindness towards animals through a narrative featuring Rover, a neglected dog who suffers mistreatment from his master, Tinker Tom. After Rover escapes and is taken in by a caring family, he experiences love and warmth for the first time. As he learns to be useful by helping to herd sheep, the story emphasizes the significance of humane treatment and education in creating a better environment for both animals and humans. Through Rover's journey, the text sets the foundation for discussing broader principles of kindness and respect for all living beings. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Animals -- Fiction; Animal welfare